The Main Role of Srs2 in DNA Repair Depends on Its Helicase Activity, Rather than on Its Interactions with PCNA or Rad51 - Bronstein, Alex (mBio, 2018)
Homologous recombination (HR) is a mechanism that repairs a variety of DNA lesions. Under certain circumstances, however, HR can generate intermediates that can interfere with other cellular processes such as DNA transcription or replication. Cells have therefore developed pathways that abolish undesirable HR intermediates. The Saccharomyces cerevisiae yeast Srs2 helicase has a major role in one of these pathways. Srs2 also works during DNA replication and interacts with the clamp PCNA. The relative importance of Srs2’s helicase activity, Rad51 removal function, and PCNA interaction in genome stability remains unclear. We created a new SRS2 allele [srs2(1-850)] that lacks the whole C terminus, containing the interaction site for Rad51 and PCNA and interactions with many other proteins. Thus, the new allele encodes an Srs2 protein bearing only the activity of the DNA helicase. We find that the interactions of Srs2 with Rad51 and PCNA are dispensable for the main role of Srs2 in the repair of DNA damage in vegetative cells and for proper completion of meiosis. On the other hand, it has been shown that in cells impaired for the DNA damage tolerance (DDT) pathways, Srs2 generates toxic intermediates that lead to DNA damage sensitivity; we show that this negative Srs2 activity requires the C terminus of Srs2. Dissection of the genetic interactions of the srs2(1-850) allele suggest a role for Srs2’s helicase activity in sister chromatid cohesion. Our results also indicate that Srs2’s function becomes more central in diploid cells.